Covalent polyphenol modification of a reactive cysteine in the major apple allergen Mal d 1. (1st June 2023) - Unterhauser, Jana; Ahammer, Linda; Rainer, Tobias; Eidelpes, Reiner; Führer, Sebastian; Nothegger, Bettina; Covaciu, Claudia E.; Cova, Valentina; Kamenik, Anna S.; Liedl, Klaus R.; Müller, Thomas; Breuker, Kathrin; et al.
Graphical abstract: Highlights: Mal d 1 is prone to spontaneous covalent modification by polyphenols. A surface-exposed cysteine residue in Mal d 1 is the primary modification site. Covalent modification does not perturb or unfold the three-dimensional structure. An immunorelevant binding epitope on the allergen surface is masked. Abstract: Naturally occurring polyphenols can modify the molecular properties of food allergens. For the major apple allergen Mal d 1 it has been postulated that chemical reactions with polyphenols cause permanent changes in the tertiary structure, causing a loss of conformational IgE epitopes and reducing allergenicity. In our study, we investigated the effect that reactions with oxidized polyphenols have on the structure of Mal d 1 by mass spectrometry and NMR spectroscopy. We showed that a surface-exposed cysteine residue in this allergen spontaneously reacts with oxidized polyphenols under formation of a defined covalent adduct. Chemical modification of Mal d 1 did not destabilize or perturb the three-dimensional fold, nor did it interfere with ligand binding to its internal pocket. A structural model of the chemically modified apple allergen is presented, which reveals that the bound polyphenol partially covers a conformational IgE epitope on the protein surface.